2015
DOI: 10.1016/j.ssi.2015.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen electrode characteristics of Pr2NiO4+δ-infiltrated porous (La0.9Sr0.1)(Ga0.8Mg0.2)O3–δ

Abstract: Pr 2 NiO 4+ δ was wet infiltrated into porous LSGM scaffolds to form solid oxide cell oxygen electrodes on LSGMelectrolyte symmetrical cells. The minimum calcination temperature required to form this nickelate phase was between 950°C and 1000°C. X-ray diffraction measurements of electrodes tested at 650°C showed little evidence of any phase change, in contrast to 650°C annealed Pr 2 NiO 4+ δ powders that decomposed to Pr 4 Ni 3 O 10 and Pr 6 O 11 . Polarization resistance followed an Arrhenius temperature depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…The Pr 2 NiO 4+δ phase starts to crystallize only when the nitrate mixture is fired at 1000°C; however, the sintering duration is not long enough to obtain the pure Pr 2 NiO 4+δ phase, some amount of Pr 6 O 11 and NiO remains. In a recent work, Railsback et al [13] observed the same tendency and found that Pr 6 O 11 was still present even after a heat treatment at 1100°C for 4 h. Such a high temperature would be harsh to apply to an infiltrated electrode, as it will strongly favor the inter-diffusion between the Pr2:Ni infiltrate and the GDC backbone or the YSZ electrolyte.…”
Section: Preliminary Experiments: Phase Formationmentioning
confidence: 74%
See 1 more Smart Citation
“…The Pr 2 NiO 4+δ phase starts to crystallize only when the nitrate mixture is fired at 1000°C; however, the sintering duration is not long enough to obtain the pure Pr 2 NiO 4+δ phase, some amount of Pr 6 O 11 and NiO remains. In a recent work, Railsback et al [13] observed the same tendency and found that Pr 6 O 11 was still present even after a heat treatment at 1100°C for 4 h. Such a high temperature would be harsh to apply to an infiltrated electrode, as it will strongly favor the inter-diffusion between the Pr2:Ni infiltrate and the GDC backbone or the YSZ electrolyte.…”
Section: Preliminary Experiments: Phase Formationmentioning
confidence: 74%
“…Concerning the nickelate materials, Nicollet et al [12] obtained for La 2 NiO 4+δ infiltrated into GDC, a polarization resistance value as low as 0.15 Ω cm 2 at 600°C. Recently, Pr 2 NiO 4+δ was used by Railsback et al [13] as the catalyst of an infiltrated electrode with La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3 δ as backbone; they measured a R p value of 0.11 Ω cm 2 at 650°C. These authors also evidenced that Pr 2 NiO 4+δ is chemically stable as an infiltrate, even though the phase is known to decompose at operating temperatures (600-800°C), as shown by Kovalesky et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Very recently, oxygen electrodes produced by PNO inltration onto an LSGM (Lanthanum Strontium Gallium Magnesium Oxide) porous scaffold have been reported. 24 In summary, although PNO is a very promising material for oxygen electrodes in SOFC/SOEC systems, its stability under real operating conditions still remains to be veried.…”
Section: Introductionmentioning
confidence: 99%
“…To solve that, Barnett and co-workers fabricated a Pr 2 NiO 4 + δinfiltrated porous La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3 −δ anode. The polarization resistance was 0.11 • cm 2 at 923 K with loading 14 vol% Pr 2 NiO 4 + δ and increased by ∼10% at 923 K during a 500-h-test in a symmetrical electrolysis cell [99] . Grenier and co-workers used Nd 2 NiO 4 + δ as the anode, 3% yttria stabilized tetragonal zirconia as the electrolyte, 30 μm-thick porous nickel and gadolinia doped ceria cermet (Ni-GDC) as cathode.…”
Section: Ruddlesden-popper Series Anodesmentioning
confidence: 98%